Occupational employment in commercial banking, 1987-90. - Kuster, Jeffrey C. (Monthly Labor Review, 1993)
Many changes in the economic and legislative climate for commercial banks occurred in the late 1980s, but the banking industry has maintained its traditional occupational staffing patterns. Spurred by increased competition, difficult economic conditions, legislative activity on the federal level, bank and savings and loan failures, and technological change, commercial banking operations underwent more consolidation between 1987 and 1990. Despite these conditions, employment in banking increased slightly during the same period. The number of general bank managers and bookkeeping and accounting clerks declined during the period between 1987 and 1990, but total employment in all other banking positions rose. Data from the 1987 and 1990 Occupational Employment Statistics surveys are presented.